Coarse-grained modeling of protein folding through simulated annealing of simplified protein backbones - Manalastas, Karen Katrina G. (College of Engineering, University of the Philippines Diliman, 2015)
We have developed Tiklop, a platform to model protein folding at low-resolution. Tiklop is a simulated annealing implementation on a simplified protein backbone representation, which samples possible conformations through constrained pivoting through five ϕ-ψ value pairs, and checks solution fitness with a knowledge-based energy function involving hydrophobic and hydrogen bonding effects. The implementation was tested on nine proteins from the Protein Data Bank, which were classified into α-helix-containing, β-sheet-containing, and mixed (α+β) proteins. Tiklop modeled α proteins with greatest accuracy, and predicted more native hydrogen-bonding contracts than another implementation using a previously-published statistical energy function. However, very little β-sheet formation was modeled, implying the possible role of long-range electrostatic interactions in facilitating β-sheet folding. Upon viewing simulated annealing intermediates for the best predicted structures, local helices were observed before tertiary structure was fully formed, consistent with current theories on protein folding dynamics. Further refinements to the energy function are recommended, in order to obtain better performance with β-sheet-containing proteins.